Introduksi Pengeringan Cabai Menggunakan Pengering Efek Rumah Kaca untuk Meningkatkan Nilai Tambah dan Pascapanen di Desa - Hikmah Yuliasari; Kavadya Syska; Ropiudin Ropiudin; Verry Verry; Feriani Budiyah; Muhammad Ridwan; Dhimas Oki Permata Aji (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity aimed to introduce a greenhouse-effect solar dryer (GESD) technology for chili postharvest processing in Kedungweru Village. The main issue faced by farmers was high postharvest losses due to unpredictable weather and conventional open sun-drying methods. The implementation included problem identification, technical training, field demonstrations, and participatory-based mentoring and monitoring. The results showed a 40–60% reduction in drying time compared to traditional sun drying, improved product quality in terms of color and hygiene, and increased selling prices by 25–35%. The activity enhanced community technical capacity in postharvest management, strengthened food resilience, and promoted village-based economic development through appropriate renewable energy technology. This model is replicable in other chili-producing regions with similar agroclimatic conditions.